Pneumococcal vaccination in diabetic patients: review from clinical practice - Amr Ghit (SpringerOpen, 2023)
Abstract The Middle East and North Africa (MENA) region has the second-highest rate of increase in diabetes, especially in KSA, Egypt, and UAE. Diabetes accounts for a significant economic burden in terms of the cost of treatment, the management of complications, disability, and the loss of productivity. Diabetic adults have an increased susceptibility to infections due to the presence of hyperglycemia. The risk of pneumonia is higher in patients with diabetes. Pneumonia caused by Streptococcus pneumoniae (pneumococcal infections) is the most frequent cause of hospitalization in KSA, which also increases the risk of mortality in diabetic patients. The annual planned pilgrimage to Mecca, KSA, is one of the largest frequent religious gatherings globally, and outbreaks of infectious diseases are of great concern. This review will discuss the pneumococcal infection outbreak and prevention in patients with diabetes in KSA. Also, it will gather information discussed by a scientific advisory board held in Riyadh in 2020 covering the current understanding of pneumococcal disease prevention in diabetic patients and recommendations to overcome barriers facing vaccination.